Is immunohistochemistry of BRAF V600E useful as a screening tool and during progression disease of melanoma patients?. Issue 1 (December 2016) - Schirosi, Laura; Strippoli, Sabino; Gaudio, Francesca; Graziano, Giusi; Popescu, Ondina; Guida, Michele; Simone, Giovanni; Mangia, Anita
Abstract Background In clinical practice the gold standard method to assessBRAF status in patients with metastatic melanoma is based on molecular assays. Recently, a mutation-specific monoclonal antibody (VE1), which detects the BRAF V600E mutated protein, has been developed. With this study we aimed to confirm the clinical value of the VE1 Ventana® antibody, as today a univocal validated and accredited immunohistochemical procedure does not exist, to preliminary detect BRAF status in our routine diagnostic procedures. Moreover, we explored the biological meaning of BRAF immunohistochemical labeling both as a predictor marker of response to target therapy and, for the first time, as a player of acquired tumor drug resistance. Methods We analyzed a retrospective series of 64 metastatic melanoma samples, previously investigated for molecularBRAF status, using a fully automatized immunohistochemical method. We correlated the data to the clinicopathologic characteristics of patients and their clinical outcome. Results The sensitivity and the specificity of the Ventana® VE1 antibody were 89.2 and 96.2% respectively, while the positive predictive value and negative predictive value were 97.1 and 86.2%, respectively. For six mutated patients the histological sample before treatment and when disease progressed was available. The immunohistochemical BRAF V600E expression in the specimens when disease progressed was less intense and more heterogeneous compared to the basal expression. Multivariate analysis revealed that a less intense grade of positive expression is an independent predictor of a less aggressive stage at diagnosis (p  = 0.0413). Conclusions Our findings encourage the introduction of immunohistochemistry as a rapid screening tool for the assessment of BRAF status in melanoma patients in routine diagnostic procedures and prepare the ground for other studies to highlight the role of immunohistochemical BRAF V600E expression in patients at the time of progression.